2018
DOI: 10.2147/copd.s151153
|View full text |Cite
|
Sign up to set email alerts
|

A functional SNP upstream of the <em>ADRB2</em> gene is associated with COPD

Abstract: BackgroundPrevious studies have suggested that β2-adrenergic receptor (ADRB2) is associated with COPD. However, the role of genetic polymorphisms in ADRB2 on COPD has not been evaluated yet.MethodsIn this study, SNaPshot genotyping, luciferase assay, chromatin immunoprecipitation and real-time polymerase chain reaction were adopted to investigate the association between ADRB2 genetic polymorphisms and COPD, comprehensively.ResultsOne single nucleotide polymorphism (rs12654778), located upstream of ADRB2, showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(47 reference statements)
0
6
1
Order By: Relevance
“…Some part of the investigations indicates, that a part of polymorphic or mutant alleles of ADRB2 gene is greater in patients with COPD, than in the control group without COPD [6]. Some authors considered a relation between the ADRV2 gene polymorphism and COPD development [18] and earlier COPD manifestation [11]. In our study we demonstrated a big part of polymorphic and mutant alleles in patients with COPD, but the weak point of our study is an absence of the control group.…”
Section: Discussioncontrasting
confidence: 57%
“…Some part of the investigations indicates, that a part of polymorphic or mutant alleles of ADRB2 gene is greater in patients with COPD, than in the control group without COPD [6]. Some authors considered a relation between the ADRV2 gene polymorphism and COPD development [18] and earlier COPD manifestation [11]. In our study we demonstrated a big part of polymorphic and mutant alleles in patients with COPD, but the weak point of our study is an absence of the control group.…”
Section: Discussioncontrasting
confidence: 57%
“… 20 It has been reported that it may be due to the genetic factors that play an indispensable role in the occurrence and development of COPD. 21 With the development of molecular biology, many genetic polymorphisms associated with lung function have been reported, such as HLA-DQB1-rs9273410, 22 TNF-A gene-308 G/A polymorphism, 23 ADRB2-rs12654778 24 and SREK1-rs74794265. 25 However, limited by race and sample size, only a small proportion of the population’s susceptibility to COPD can be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Several GWAS have reported that multiple SNPs in the CXCL10 , 12 ADRB2 , 13 HHIP , 14 and SERPIN2 15 genes contribute to COPD susceptibility. However, association of the SNPs in the SREK1 gene with COPD is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%